PENGARUH PAJAK, SUBSIDI DAN ZIS TERHADAP PENURUNAN KEMISKINAN DI INDONESIA - Hikmathiar Ramadhan; Tatik Mariyanti (Media Ekonomi, 2014)
This paper discusses the analysis of the effect of taxes and subsidies and ZIS (Zsakat, Infaq and Sedekah) to the reduction of poverty in Indonesia in the period 1994 to 2013. The variables used in include taxes, subsidies, ZIS and poverty of the State of Indonesia. The method used in this thesis is a multiple regression method along with the classical assumptions. This study aims to determine the relationship between variables taxes, subsidies and ZIS against poverty. In addition, this study also aims to look at the variables which play a role in reducing poverty. The results using multiple regression analysis, it appears that all the independent variables are not significant and have adjusted R-square is nice. Next to the classical assumption test, based on the results of research there is a violation of classical assumptions in this research is the Normality.